Youth resistance training: updated position statement paper from the National Strength and Conditioning Association - Faigenbaum, A. D.; Kraemer, W. J.; Blimkie, C. J.; Jeffreys, I.; Micheli, L. J.; Nitka, M.; Rowland, T. W. (The Journal of Strength and Conditioning Research, 2009)
Current recommendations suggest that school-aged youth should participate daily in 60 minutes or more of moderate to vigorous physical activity that is developmentally appropriate and enjoyable and involves a variety of activities (219). Not only is regular physical activity essential for normal growth and development, but also a physically active lifestyle during the pediatric years may help to reduce the risk of developing some chronic diseases later in life (196). In addition to aerobic activities such as swimming and bicycling, research increasingly indicates that resistance training can offer unique benefits for children and adolescents when appropriately prescribed and supervised (28,66,111,139,147,234). The qualified acceptance of youth resistance training by medical, fitness, and sport organizations is becoming universal (5,6,8,12,18,33,104,167,192,215).